TRADISI SASTRA PROPHETIK DAN PENINGKATAN TRADISI KEAGAMAAN - Wargadinata, Wildana (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2008)
Glorifying our prophet, respecting and loving him cannot be omitted from the heart of Moslem people in all over the world. In Islam history, the love expression to our prophet is realized in the from of, among other thing, a literary work that is known as Al-Madaih Al-Nabawiyah. In Indonesian (Javanese) tradition, Al-Madaih is a accepted and grows fast in the form of sholawatan. Sholawatan tradition, especially in Java, is conducted in various religious rituals.